2020
DOI: 10.1177/0333102420937655
|View full text |Cite
|
Sign up to set email alerts
|

Two-hour infusion of vasoactive intestinal polypeptide induces delayed headache and extracranial vasodilation in healthy volunteers

Abstract: Background In recent years, vasoactive intestinal peptide (VIP) and pituitary adenylate cyclase-activating polypeptides (PACAPs) have gained special interest in headache science. VIP and PACAPs (two isoforms, PACAP27 and PACAP38) are related in structure and function, as are their receptors, but they show differences in vasodilating- and headache-inducing properties. Intravenous infusion of PACAP27 or PACAP38, but not VIP, induces a long-lasting dilation of cranial arteries and delayed headache. The relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 41 publications
1
40
0
Order By: Relevance
“…A total of 943 articles were screened by title and abstract. Of these, 27 studies met the inclusion criteria (1994 and 2020) and were included in the qualitative and quantitative analysis (935) (Figure 1). Twelve studies (10 published and two studies under review) reported data on the incidence of migraine attacks after placebo in individuals with migraine without aura (917,31,33), whereas 10 studies did so in healthy volunteers (18,19,22,23,25,27,29,30,32,34).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 943 articles were screened by title and abstract. Of these, 27 studies met the inclusion criteria (1994 and 2020) and were included in the qualitative and quantitative analysis (935) (Figure 1). Twelve studies (10 published and two studies under review) reported data on the incidence of migraine attacks after placebo in individuals with migraine without aura (917,31,33), whereas 10 studies did so in healthy volunteers (18,19,22,23,25,27,29,30,32,34).…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies (10 published and two studies under review) reported data on the incidence of migraine attacks after placebo in individuals with migraine without aura (9-17,31,33), whereas 10 studies did so in healthy volunteers (18,19,22,23,25,27,29,30,32,34). Furthermore, 16 studies reported data on the incidence of delayed headache after placebo in healthy volunteers (13,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)32,34). A summary of the included studies is presented in Table 1 and Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our plasma VIP findings are consistent with these previous reports, although our results were observed in pediatric migraineurs. Another clinical study recently demonstrated that more prolonged VIP-mediated vasodilation provokes more headache than shorter vasodilation (34). Considered together, PACAP-38 and VIP may contribute to migraine pain through both vasodilation and dural mast cell degranulation.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that, similar to our results when testing PACAP-27, VIP can also induce light aversive behavior in mice if measured immediately after administration, consistent with its shorter half-life compared to PACAP (Mason et al, 2020). This suggests that the VPAC receptors are capable of inducing migraine-like phenotypes in mice, which has recently been validated by prolonged VIP infusion causing delayed headache in people (Pellesi et al, 2020). Alternatively, it is possible that PACAP-38 involvement in migraine may be independent of the VPAC or PAC1 receptors.…”
Section: Discussionmentioning
confidence: 96%